Study on Technical, Behavioral and Organizational Factors Affecting the Performance of Mother and Child Tracking System in Rural Area of Varanasi District, Uttar Pradesh: A Qualitative Study - Verma, Pooja; Kansal, Sangeeta; Sarkar, Madhutandra; Kesh, Nishu; Kumar, Alok (Indian Journal of Community Health, 2020)
Background: The Mother and Child Tracking System (MCTS) portal captures and tracks all pregnant women right from conception up to 42 days after delivery and all children below five years. Objectives: This study was conducted to find out the technical, behavioral and organizational factors that affect the process and performance of MCTS. Material and Methods: This was an exploratory qualitative study conducted in Varanasi district by using multistage random sampling method. Data were collected by in-depth interviews of 48 health care providers. Results: Majority of the ANMs and ASHAs were not aware of the meaning of “Tracking System” and the use of MCTS ID. Inappropriate training of ASHAs, absence of supervision and monitoring by ANMs, overburdened DEOs and ANMs, poor internet connection, slow server speed, software problem and frequent power failures were identified as major factors for poor performance of MCTS. Conclusion: The most effective measure to improve the performance of MCTS would be to properly train grass root level workers so that more efficient data can be fed into MCTS.